IMPLEMENT LEARNING MODEL COOPERATIVE TYPE TEAMS GAMES TOURNAMENT (TGT) IN CONTENT TYPES OF STYLE IN STRUCTURAL BUILDING CLASS X ENGINEERING CONSTRUCTION CONCRETE STONE SMKN 1 PALANGKA RAYA 2016/2017 - Pronasi; Whendy Trissan (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2017)
This research was motivated by student learning outcomes in a variety of styles materials in building structures of class X Stone and Concrete Construction Engineering SMK Negeri 1 Palangka Raya. It has not been as expected, such as learning results of class X TKBB 2013/2014 school year in which the school year 2014 / 2015 and 2015/2016 school year were only 43.47%, 54.16%, and 53.57% of students who meet the KKM and other students have not reached the KKM standard achievement. This is caused that students are more tending to be passive, silent and less involved in the learning process. The purpose of this study was to determine student learning outcomes after implementing cooperative learning model type Teams Games Tournament (TGT). This research is a descriptive study, in which data used in this research is quantitative data in the form of the final test. The data were analyzed using individual mastery and classical completeness. The research was conducted on September 5, 2016 to the date of October 3, 2016. The subject of the study 25 students of class X TKBB SMK 1 of Palangka Raya in Academic Year 2016/2017. The instrument used in this study is the final test. Problem final test of 40 multiple choice questions. Each end of the test items have been reviewed by three people in which consisting of two lecturers from vocational technology education Palangka Raya University and a teacher of engineering mechanics TKBB class X SMK Negeri 1 Palangka Raya to obtain validity matter. This study shows that student learning outcomes by the end of the test obtained by the level of achievement of 73.6%, there are 20 students completed (80%), and 5 students did not complete (20%). Classical completeness students have achieved. It concluded that the student learning outcomes were improved after applying the type cooperative learning TGT